Paradigm of Religious-Conservative Education Thought from KH Hasyim Asy'ari's Perspective - Nur Rahma Bt Amran; Zian Salsabila Bidaula (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
KH. Hashim Asy'ari as a Muslim intellectual, introduced the results of his thoughts in the field of Islamic education as an aspect of life formed in the religious field. He implemented an education system based on the Qur'an and as-sunnah as guidelines. This article aims to analyze the Paradigm of Religious-Conservative Education Thought from the KH. Hashim Ash'ari perspective. This research is qualitative research in the form of literature study. The object of this study is the concept of KH thinking. Hashim Asy'ari on Islamic education. The results showed that Islamic education in the perspective of KH. Hashim Asy'ari is patterned on traditional Islam or known as Religious-Conservative which emphasizes the values of Sufism which is divided into three fields, namely Sufism, theology and fikqh. This is very different from modernist ideas, until the works he wrote adhered to religious-conservative beliefs.